Da retextualização das narrativas orais de pé de serra ao RPG: nas trilhas dos multiletramentos - Santos, Sandra Maria Carneiro (2019)
The master dissertation entitled From the Retextualization of the Oral Narratives of Pé de Serra to the RPG: in the tracks of multiletracy presents a project of pedagogical intervention, the report of its application, the description and analysis of the results. The aim of the pedagogical intervention was to expand the linguistic and discursive skills of students from the 9th grade of Elementary School through the Role Playing Game, the RPG, starting from the retextualization of the oral narratives of Pé de Serra, with a view to expanding multiliteracies. The intervention proposal, inspired by action research, was applied at the Luís Eduardo Magalhães Municipal School, in the town of Pé de Serra-BA. The theme of the intervention came from the experience of the author of this dissertation, which has been teaching Portuguese Language for 21 years, and was motivated by the need to stimulate reflection about the current scenario of multiplicity of cultures and multimodalities of texts that students are inserted. In this regard, it is up to the school to consider the diversity that permeates the daily life of the subject and the ways by which he is informed and communicated in a connected society. Based on this reflection, the project was based on the trails of Multiliteracies Pedagogy proposed by the New London Group in 1996 and presented here in Brazil by Rojo and Moura (2012), aligning the execution of the Didactic Sequence, based on Cosson (2012) and Dolz and Scheneuwly (2004), to the four aspects of Pedagogy: Embedded Practice, Explicit Instruction, Critical Framework and Transformed Practice, contemplated in the various stages of the project. This journey allowed the alliance between the memories of the community considered in the research and the collective construction of new stories, through the incorporation of technologies already used by the students. To that end, the intervention was based on the re-contextualization of oral narratives of local tradition, based on the studies of Marcuschi (2010), and reached the collective writing of narratives of adventures through the RPG in the Whatsapp application, culminating in the book launch containing the memories and the stories, aiming at the dissemination and recording of the narratives. A website was also prepared, available at the link: http://smcarneiropb.wixsite.com/prosandramaria contemplating the dissemination of the stages of the project and aiming to disseminate the knowledge acquired through it. Thus, through evaluation and analysis of the activities, it was realized that the objectives were achieved at various levels, proving that the recognition and appreciation of the social experiences of the subject, the technologies that permeate his life and the systematic study of the language favor the development of multilteracies.